Keys to the Council : Unlocking the Teaching of Vatican II - Gaillardetz, Richard R., 1958- (Book collections on Project MUSE., 2012)
"As the church marks the fiftieth anniversary of the opening of the Second Vatican Council, too few Catholics have an adequate grasp of what the council contributed to the life of the church. The problem is understandable. The Second Vatican Council produced, by far, more document pages than any other council. Consequently, any attempt to master its core teachings can be daunting. There is a danger of missing the forest for the trees. With this in mind, Keys to the Council identifies twenty key conciliar passages, central texts that help us appreciate the vision of the council fathers. Each chapter places the given passage in its larger historical context, explores its fundamental meaning and significance, and finally considers its larger significance for the life of the church today. Chapters include exploration of Sacrosanctum Concilium's demand for "full, conscious, and active participation" in the liturgy; Lumen Gentium's eucharistic ecclesiology; Gaudium et Spes's vision of marriage as an intimate partnership of life and love; Nostra Aetate's approach to non-Christian religions; and more."--Publisher description.